2022
DOI: 10.1111/ppl.13670
|View full text |Cite
|
Sign up to set email alerts
|

Defects in meristem maintenance, cell division, and cytokinin signaling are early responses in the boron deficient maize mutant tassel‐less1

Abstract: Meristems house the stem cells needed for the developmental plasticity observed in adverse environmental conditions and are crucial for determining plant architecture. Meristem development is particularly sensitive to deficiencies of the micronutrient boron, yet how boron integrates into meristem development pathways is unknown. We addressed this question using the boron‐deficient maize mutant, tassel‐less1 (tls1). Reduced boron uptake in tls1 leads to a progressive impairment of meristem development that mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 104 publications
1
10
0
Order By: Relevance
“…The fact that the CK forms with a high affinity to shoot CK receptors accumulated exclusively in the B-efficient accession, while the less active form DZR and the deactivated species CZROG and TZOG accumulated in the B-inefficient accession, points to a shoot growth-regulating role of these CK species, especially under low B. This conclusion is in line with the recent finding that CK signaling regulates early responses of B deficiency in maize, where a B-dependent CK signaling was shown to be important to prevent the progressive impairment of meristem development revealed by vegetative and reproductive defects (Matthes et al, 2022). Moreover, overexpression of a CK oxidase in maize roots, which leads to reduced CK levels, was shown to influence the shoot content of various nutrients (Ramireddy et al, 2021).…”
Section: Cks As Early B Deficiency Signals In B-efficient Oilseed Rapesupporting
confidence: 85%
“…The fact that the CK forms with a high affinity to shoot CK receptors accumulated exclusively in the B-efficient accession, while the less active form DZR and the deactivated species CZROG and TZOG accumulated in the B-inefficient accession, points to a shoot growth-regulating role of these CK species, especially under low B. This conclusion is in line with the recent finding that CK signaling regulates early responses of B deficiency in maize, where a B-dependent CK signaling was shown to be important to prevent the progressive impairment of meristem development revealed by vegetative and reproductive defects (Matthes et al, 2022). Moreover, overexpression of a CK oxidase in maize roots, which leads to reduced CK levels, was shown to influence the shoot content of various nutrients (Ramireddy et al, 2021).…”
Section: Cks As Early B Deficiency Signals In B-efficient Oilseed Rapesupporting
confidence: 85%
“…Ince et al (2018) determined that the in vivo effects of boron on mRNA expression of OCT‐3/4, NANOG, and HEX genes in embryo and histological changes along fetal development. Matthes et al (2022) found that meristem maintenance, cytokinin signaling, and cell division as a result of boron insufficiency in maize mutant, tassel‐less1 (tls1).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, boron may have the potential to act in specific genes, domains, homeoproteins (as homeobox domain products), or transcription factors Ince et al (2018). determined that the in vivo effects of boron on mRNA expression of OCT-3/4, NANOG, and HEX genes in embryo and histological changes along fetal development Matthes et al (2022). found that meristem maintenance, cytokinin signaling, and cell division as a result of boron insufficiency in maize mutant, tassel-less1 (tls1).5 | CONCLUSIONOverall, our study showed that both B 2 O 3 NPs and its ionic form could exert certain detrimental effects on D. melanogaster at relatively high exposure doses, which highlights the significance of thorough examination and risk assessment of B 2 O 3 NPs for the first time.…”
mentioning
confidence: 99%
“…One clear phenotype of B deficiency is the inhibition of root elongation (Poza-Viejo et al, 2018). Previous studies have shown that B deficiency affects normal physiological activities in the shoot, including impaired photosynthesis in MC (Figure 4d) (Han et al, 2008), impeding nutrient absorption and transport by affecting the stability of vascular bundles (Pommerrenig et al, 2019), and restricting the development of root meristem (Matthes et al, 2022). However, observing the effects of B deficiency on different cell types in the shoot apex at the single-cell transcript level is a novel aspect of this study.…”
Section: Shoot Apex Cells Exhibit Varying Responses To B Deficiencymentioning
confidence: 99%
“…Research has shown that meristem development is particularly sensitive to B deficiency (Poza‐Viejo et al., 2018). The reduced‐B‐uptake mutant tassel‐less1 ( tls1 ) in Z. mays exhibits defective SAM structure due to transcriptional repression of the meristem maintenance gene KN1 and cell cycle genes (Matthes et al., 2022). However, how B deficiency affects the regulation of meristem development and the key TFs involved in this process have yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%